Dissipation factor measurement of PILC insulation at UHF - Raymond W.J.K.; Chakrabarty C.K.; Hock G.C.; Ghani A.B.; Zarim Z.A.A. (2023)
In this paper, dissipation factor measurement of Paper Insulated Lead Covered (PILC) cable insulation at ultra high frequency (UHF) is described. The material under test (MUT) is clamped between two copper sheets to form a capacitor, which is connected to the Advantest R3767CG vector network analyzer (VNA) to measure its input impedance at the resonant frequency. From the input impedance, the dissipation factor is calculated. The calculated values are then compared with data obtained from commercial system to validate the proposed method. 2012 IEEE.